Eugen Fink’s understanding of the transcendental I - Łaciak, Piotr (Folia Philosophica, 2011)
The paper deals with Eugen Fink’s interpretation of transcendental I. Fink does not make do with traditional phenomenological distinction between natural I and transcendental I, but within transcendental I he looks for the distinction between constitutive I (konstituierendes Ich) i phenomenologizing I. Hence, according to Fink, we should distinguish three kinds of I: natural I (trapped in the world), transcendental I which constitutes the world and transcendental-phenomenologizing I (transzendental-phänomenologisierendes Ich) as theoretical spectator, who meets the conditions of phenomenological reduction but does not contribute to the constitution of the world. Finks interpretation of transcendental I aims at overcoming difficulties related to Husserlian phenomenological reduction, and the distinction of constitutive I and phenomenologizing I was accepted by Husserl himself.